TAHAPAN J.BRUNER DALAM PEMBELAJARAN MATEMATIKA PADA PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DI SEKOLAH DASAR (SD/MI) - Widyaningrum, Retno (IAIN Ponorogo, 2011)
Teaching is not only changing ones behavior but more importantly it function to change the school curriculum on such a way that students can learn easily and optimally. It is essential to take an action to improve the studentsâ ability in math based on their own nature development, particularly in primary schools level. This can be gained by creating the students active participation and regarding their diversity of as conveyed by J. Bruner. In order to improve the quality of learning process, it is necessary to set up a convenience environment known as